Effect of Cobactin on the feedlot performance and carcass traits of beef steers - L. Corah; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1988)
The addition of Cobactin to feedlot rations had no significant effect on average daily gain or feed efficiency, but did improve quality grade of steers fed for 110 days.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Cobactin; Feedlot performance; Carcass traits; Steers